Evolution of structural indicators. China and regions: 1981 - 2010 - Jose Miguel Albala-Bertrand (Queen Mary University of London, School of Economics and Finance, 2013)
This paper deals with some structural indicators and their evolution, in China and regions, over the period 1981-2010. We first produce estimates of the optimal productivities of incremental capital and the optimal incremental income elasticity of capital by means of a linear programming exercise. We then produce an accounting growth decomposition to assess the changes in the contribution of capital productivity, capital intensity and labour participation to the growth rate of output per capita. Finally, we combine an accounting growth decomposition with a standard production function, growth accounting, decomposition to assess both the contribution of both capital productivity and capital intensity to total factor productivity (TFP). We also show in an appendix the difference in the TFP growth contribution when marginal elasticities are assumed variable over time and when scale returns are assumed increasing rather than constant. Our main conclusion is that capital intensity, rather than capital productivity or labour participation, has been the main growth contributor. But this does not mean that quantity in itself, rather than quality, is behind such growth, as total factor productivity, which is significantly more than engineering technical change, has been relatively important over the period.
Keywords: O4; B4; E2; 330; Structural indicators; Incremental capital productivity; Growth decomposition; Optimal consistency method (OCM); Total factor productivity (TFP)